A participatory climate vulnerability assessment for recreational tidal flats fisheries in Belize and The Bahamas - Carroll, Gemma; Eurich, Jacob G.; Sherman, Krista D.; Glazer, Robert; Braynen, Michael T.; Callwood, Karlisa A.; Castañeda, Adriel; Dahlgren, Craig; Karr, Kendra A.; Kleisner, Kristin M.; Burns-Perez, Virginia; Poon, Sarah E.; et al. (Frontiers in Marine Science, 2023)
Recreational fishing is a pillar of the multibillion-dollar tourism sector in the Caribbean, supporting economic development and community livelihoods. However, as climate change drives increased habitat degradation, key recreational target species may experience declines. To effectively prioritize adaptation and mitigation efforts it is critical to project climate change impacts on recreational species and the communities that depend on them. We conducted a comprehensive climate vulnerability assessment (CVA) for three recreationally important tidal flats species in Belize and The Bahamas: bonefish (Albula vulpes), tarpon (Megalops atlanticus), and permit (Trachinotus falcatus). Species vulnerability was assessed by coupling 1) a research-based CVA to evaluate the sensitivity and exposure of species to climate impacts with 2) a participatory workshop involving 17 fishing guides, resource managers, and science and policy experts working in fisheries systems in Belize and/or The Bahamas. The workshop elicited local expert knowledge to resolve and contextualize CVA scoring and to identify strategies to increase climate resilience. Based on the CVA, climate impacts in the Caribbean are expected to be ‘very high’ in magnitude by 2050. All three species exhibit ‘very high’ vulnerability to these changes based on life history traits and reliance on nearshore habitats that are exposed to rapid temperature increases and storm damage. The expert stakeholder group confirmed a ‘very high’ magnitude of expected climate impacts in the Caribbean region, to which bonefish, the most valuable species, is likely to have a ‘very high’ vulnerability. However, stakeholders perceived tarpon and permit to be less vulnerable to these impacts than the CVA predicted, based on “on the water” observations of their habitat flexibility and resilience to disturbance. The group identified strategies at the individual, community, national, and international levels to enhance climate resilience in the recreational fishing sector. Our work highlights how participatory CVA processes can support a stronger understanding of species’ vulnerability while building capacity and collaboration to increase climate change readiness.